Impact Of Foliar Application Of Micronutrients On Some Biochemical Parameters Of Mulberry (Morus Alba L.) (Applied Biological Research, 2015)
The present study was aimed to assess the impact of foliar application of  various micronutrients viz., Fe, Zn, Mn, B and Mo, sprayed individually  and in combination, on the qualitative characteristics of mulberry leaves. The experiment was conducted in 2011-2012 and quality parameters  assessed 45 days after pruning. The results revealed that all the individual  applications of above micronutrients significantly improved moisture,  moisture retention capacity, chlorophyll ‘a’ and ‘b’ and total chlorophyll,  carotenoids, nitrogen, phosphorus, potassium, zinc, iron, boron,  manganese, crop growth rate and net assimilation rate over control. The  combined foliar application of 0.5% ZnSO4 + (1.0% FeSO4 + 0.1% citric  acid) + 0.2% boric acid+ 0.5% MnSO4 + 0.01% Na2MoO4 was most  effective in improving mulberry leaf quality.
Keywords: Chlorophyll; foliar spray; leaf quality micronutrients; mulberry